Problemas de compreensão no texto falado : uma busca pela intercompreensão - Neumann, Daiane (2008)
This research intends to clarify how the comprehension is built from comprehension problems which arise during the conversation. The spoken text is characterized by its production conditions. The planning and the production are not stages that succeed, but they are simultaneous in spoken language. This condition will leave traces on the spoken text of a constant search for the intercomprehension. Through the analysis of these traces left on the text, we can find problems of prospective and retrospective nature. The first ones are repaired by activities called verbalization, that is, interruption, false starts, incomplete utterances, hesitation phenomena, while the second ones are repaired by activities called treatment activities, among them, paraphrases, repetitions and corrections. Finally, we have the qualification procedures which are commenting procedures of the interlocutor s utterances. The verbalization, treatment and qualification procedures are responsible for the prophylatic comprehension monitoring, which means, they have the function of avoiding and/or repairing problems that can arise during the interactional process. However, the linguistic diversity, the lack of knowledge of other s beliefs and knowledge, the cultural and ideological differences, the different degree of the knowledge about the subject in hand, make the speakers usually have comprehension problems during the communication process, that is, make the speakers deal with situations where one of them express his/her non-comprehension about the interlocutor s utterance. To develop this work, we will analyze spoken texts, recorded and wrote out by researchers from NURC (Norma Urbana Culta) project, pursuing the goal of describing the interaction processes which the speakers use to solve the comprehension problems that arise in spoken text, specifically, describing the source of the problems and the linguistics procedures which are used to solve them